2013
DOI: 10.1590/s1516-35982013000400001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of agronomic characters in Panicum maximum hybrids

Abstract: -This study was carried out with the objective of estimating the genetic parameters of agronomic traits in Panicum maximum hybrids. Genotypes obtained from the crosses between the sexual plants S10 and S12 and cultivars Tanzania and Mombasa were evaluated. The design was an incomplete blocks design with two replicates (clones) and 33 blocks. Each block was constituted by three lines or plots with nine plants each, which were evaluated in six harvests. All the characters presented low broad sense heritabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
(7 reference statements)
1
10
1
Order By: Relevance
“…Gains with selection should be high for productivity during the dry season in this population, since FGW and TDM showed high magnitudes of heritability estimates, 0.74 and 0.65, respectively. These estimates were of greater magnitude than those observed for B. humidicola and Panicum maximum (Figueiredo et al 2012, Braz et al 2013, also evaluated for TDM in the dry season.…”
Section: Fi Matias Et Alcontrasting
confidence: 53%
See 2 more Smart Citations
“…Gains with selection should be high for productivity during the dry season in this population, since FGW and TDM showed high magnitudes of heritability estimates, 0.74 and 0.65, respectively. These estimates were of greater magnitude than those observed for B. humidicola and Panicum maximum (Figueiredo et al 2012, Braz et al 2013, also evaluated for TDM in the dry season.…”
Section: Fi Matias Et Alcontrasting
confidence: 53%
“…The opposite happened for REG with estimates of 0.37 for the dry and 0.42 for the rainy season (Table 1). Estimates of low magnitude of r i for REG were also observed for Panicum maximum in a joint analysis considering seven clippings (Braz et al 2013). …”
Section: Fi Matias Et Almentioning
confidence: 68%
See 1 more Smart Citation
“…Also, according to these authors, the hybrids with worst performance were those from the S12 × T110 cross. Trend of progenies originating from the most productive parents obtaining greater TDM and LDM in the P. maximum species is related to the considerable level of heritability reported for these parameters (RESENDE et al, 2004;BRAZ et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The leaf spots presented characteristics of damages caused by Bipolaris sp. In general, other studies report the susceptibility of these grasses to attacks of fungi from genre Bipolaris, Exserohilum and Curvularia, which cause spots in leaves and stalks, besides drying the leaves and killing the seedlings (Macedo and Barreto, 2007;Martinez et al, 2010;Kleczewski et al, 2012;Braz et al, 2013;Kumar et al, 2013), however, some authors realized that this result may vary in accordance with the genotype used (Braz et al, 2013). Yago et al (2011) observed that there was an increase in the seedling death percentage for sorghum and foxtail millet seeds inoculated with Curvularia lunata and increase in the severity index for infected seedlings 10 days after the inoculation.…”
Section: Pathogenicitymentioning
confidence: 99%